Crosstalk between Bcl-2 family and Ras family small GTPases: potential cell fate regulation? - Kang, Jia; Pervaiz, Shazib (Frontiers in Oncology, 2013)
Cell fate regulation is a function of diverse cell signaling pathways that promote cell survival and or inhibit cell death execution. In this regard, the role of the Bcl-2 family in maintaining a tight balance between cell death and cell proliferation has been extensively studied. The conventional dogma links cell fate regulation by the Bcl-2 family to its effect on mitochondrial permeabilization and apoptosis amplification. However, recent evidence provide a novel mechanism for death regulation by the Bcl-2 family via modulating cellular redox metabolism. For example overexpression of Bcl-2 has been shown to contribute to a pro-oxidant intracellular milieu and down-regulation of cellular superoxide levels enhanced death sensitivity of Bcl-2 overexpressing cells. Interestingly, gene knock down of the small GTPase Rac1 or pharmacological inhibition of its activity also reverted death phenotype in Bcl-2 expressing cells. This appears to be a function of an interaction between Bcl-2 and Rac1. Similar functional associations have been described between the Bcl-2 family and other members of the Ras superfamily. These interactions at the mitochondria provide novel opportunities for strategic therapeutic targeting of drug resistant cancers.